Pseudo‐single‐atom Platinum Induced by the Promoter Confined in Brucite‐like Lattice for Catalytic Reforming. Issue 10 (29th April 2016) - Ma, Xiaodan; An, Zhe; Zhu, Yanru; Wang, Wenlong; He, Jing
Abstract: Pseudo‐single atom Pt catalysts have achieved an excellent selectivity to branched paraffins and cycloalkanes in n ‐hexane reforming here. Highly dispersed platinum in single‐atom and small clusters made up of several separated atoms was produced under the inducement of Sn or Zr as promoting components. The Sn or Zr oxides were topologically transformed from layered double hydroxides as precursors, and thus homogeneously dispersed owing to the confinement of the brucite‐like lattices. The lattice confinement also caused the promoter sites charge‐transferred, affording electron‐rich (Sn) or electron‐defected (Zr) sites on the surface, thereby facilitating the inducement to Pt sites. This strategy provides an effective and feasible alternative for the facile preparation of highly dispersed metal catalysts. In n ‐hexane reforming, a selectivity of up to 95 % to branched paraffins and cycloalkanes was obtained with the pseudo‐single‐atom Pt catalysts. Abstract : A site for sore eyes ! The excellent dispersion of the promoter components results from the confinement effects of brucite‐like lattices, and the selective inducement originates from the strong interactions between Sn IV or Zr IV sites and Pt sites. In the catalytic reforming of n ‐hexane, pseudo‐single‐atom Pt afforded a selectivity of up to 95 % to iso‐alkanes and cycloalkanes, whereas the contrast samples with larger Pt sites performed a lower selectivity to iso‐alkanes and cycloalkanes, but generated undesired C1–C5 and benzene.